EFFECT OF NUTRIENT SOLUTION FLOW INTERVAL ON GROWTH AND YIELD OF LETTUCE (Lactuca sativa) GROWN IN HYDROPONICALLY DEEP FLOW TECHNIQUE - Ningrum, Suci Sapta; Saleh, Ismail; Budirokhman, Dodi (AGROSCRIPT: Journal of Applied Agricultural Sciences, 2019)
Lettuce (Lactuca sativa L.) is one of the vegetables that are commonly cultivated by using hydroponic systems. Some hydroponic systems require high current expenses in particular for the electricity in order to circulate nutrient solution e.g. in the water culture system – deep flow technique (DFT) -. Electricity costs can be reduced by changing from continuous nutrient flow to intermittent nutrient flow. The aim of this research was to investigate the effect of interval nutrient flow on growth and yield of lettuce. The experiment was conducted in Cirebon from February to April 2018. The experiment was arranged by using randomized complete block design with four treatments: (i) continuous nutrient flow (control), intermittent nutrient flow (nutrient flow during (ii) 15 minutes, (iii) 30 minutes, and (iv) 45 minutes). For each intermittent treatment, the nutrient flow was interrupted for 60 minutes. Each treatment was repeated four times. The result showed nutrient flow interval affected to plant height, shoot diameter, and leaf area at 35 days after planting (DAP). Meanwhile, leaves number, root volume, and fresh weight of harvested crops were not significantly different in all nutrient interval treatments. The highest plant height and shoot diameter were detected in the treatment (ii) nutrient flow during 15 minutes and interruption for 60 minutes, the results were not significantly different to the control – continuous flow treatment. It can be concluded the interval nutrient flow can be used as an alternative of the continuous flow of nutrient solution in hydroponically DFT.